Pesemsko obveščanje in ustvarjanje tradicije - Klobčar, Marija (Traditiones (Ljubljana), 2014)
In the quest for ethnic identification, ballads played an exceptionally important role, which was also based on their aesthetic evaluation. Transcriptions of songs from the first half of the nineteenth century focused on the lyrics, and so the assessment of the creators of ballads and their bearers was shaped based on the situation when these songs were still only preserved in the countryside. This perspective was in line with the concept of the rural population as the creators of folk tradition. However, taking into account social circumstances, evidence regarding the existence of broadsides, and lyrical and melodic characteristics, it is clear that certain ballads were to a large extent created by professionals and also based on printed material. When they were being created, these ballads were also widespread among young people as popular songs and also in the urban environment, which points to the importance of towns in this tradition not only in the present, but also in the past.
Keywords: ethnology; etnomuzikologija; folk songs; slovenske ljudske pesmi; folk tradition; slovenska ljudska glasba; ljudski pevci; popular culture; ljudsko izročilo; Slovenia; Slovenija; zgodovinski pregledi